Review of English as a lingua franca: Perspectives and prospects. Contributions in honour of Barbara Seidlhofer; Editors: Marie-Luise Pitzl, Ruth Osimk-Teasdale; Publisher: Mouton de Gruyter, 2016; ISBN: 9781501511226; Pages: 294 - Vettorel, Paola (Studies in Second Language Learning and Teaching, 2016)
Book review